Jenis-Jenis Insiden Keselamatan Pasien di Pusat Kesehatan Masyarakat - Shinta Nuria; Inge Dhamanti (Media Gizi Kesmas, 2023)
Background: Developing a patient safety culture in the public health center is less significant than in hospitals. According to WHO, primary care services can prevent up to 80% of injuries, which accounts for half the global burden of patient injury. Objectives: This study aims to determine the type of patient safety incidents in public health centers in Surabaya. Methods: This research is classified as descriptive-analytic research with a cross-sectional research design, used secondary data collected through the monthly reports of "Public Health Center X" located in Surabaya in the period from January to July 2022. Results: The frequency of patient safety incidents was 65 cases consisting of order entry error (10.76%), administration error (24.61%), human error (10.76%), medical error (3.07%), healthcare-acquired infection (6.15%), patient falls (18.46%), medication error (13.84%) and technical error (12.3%). Most patient safety errors were considered preventable, and 29% of the errors from human error and patient falls were viewed as having the potential to cause serious harm to the patients. Conclusions: The types of patient safety errors are mostly administration errors, that occur in the management of medical record documents.